Behavioural and neuroimaging changes after naming therapy for semantic variant primary progressive aphasia. (August 2016) - Jokel, Regina; Kielar, Aneta; Anderson, Nicole D.; Black, Sandra E.; Rochon, Elizabeth; Graham, Simon; Freedman, Morris; Tang-Wai, David F.
Abstract: The objectives of this study were to examine the effects of a successful naming intervention on naming performance and brain activity in individuals with the semantic variant of primary progressive aphasia (svPPA). Four participants with svPPA were scanned while performing phonologically- and semantically-based tasks before and after an intense, 20-h naming therapy that followed the principles of errorless learning whereby errors were eliminated from the learning process. Five healthy control participants were scanned at the outset of the study and did not receive treatment. The results showed that in svPPA participants, successful re-learning of forgotten vocabulary was accompanied by activation of a larger network in bilateral brain regions and that the level of activation in the left anterior lobe may be inversely correlated with severity of semantic impairment. Our findings have implications for treatment in svPPA patients and suggest that semantic cues can improve naming, in spite of significant semantic impairment. The results indicate that intensive language therapy can lead to behavioural gains and neuroplastic changes even in individuals with more advanced anterior temporal lobe atrophy. Highlights: Treatment for naming impairments in svPPA results in improvements. Behavioural intervention results in neuroplasticity in svPPA. Semantic processing in svPPA recruits bilateral brain regions. Activation in the left ATL is inversely related to severity of language impairment.